Experiências formativas no início da docência mediadas pelo PIBID educação física da Universidade Estadual de Feira de Santana, Bahia - Melo, Tatiana Moraes Queiroz de (2015)
The present work aims to understand how the Coordinator, the Supervisors and the Fellows of the PIBID Physical Education from the State University of Feira de Santana (UEFS) in the city of Feira de Santana - Bahia understand the processes in teaching initiation in initial teacher training of Physical Education in the PIBID Physical Education - UEFS. Through the Narrative Research in a research and training perspective, we give opportunity of narrative interviews composed of the necessary critical reflexivity in the constitution of teaching to the research subjects. We analyzed the academic productive about teaching initiation at the time of initial formation on the databases of the National Association of Graduate Studies and Research in Education (ANPED) and the Brazilian Sports Science Congress (CONBRACE) and we also discussed with Antonio Novoa, Carlos Marcelo and Molina Neto about training concepts and lived experiences in the teaching initiation and we seek Walter Benjamin and Jorge Larrosa to anchor understanding of the concept of experience. The results point to the recognition of PIBID as a program that brings closer the playing field interfering in the choice for teaching. Indicate that the program enables the articulation between the university and the school to strengthen the training prospect that happens collectively. And confirm that the PIBID allows the verification of challenges present in the school and the necessity of transforming this reality with the articulation of academic and school knowledges. In this sense, we notice the affirmation of career entry, as a formative experience that intensifies the professional development of teachers and, therefore, it must be designed as an institutionalized nacional policy in teaching initiation.